The Effect of Product Quality and Customer Perceived Value on Repurchases with Intervening Satisfaction - Noviana, Isnabillah; Oktavia, Dinda (SAN Scientific, 2023)
The purpose of this study was to determine the effect of product quality and customer-perceived value on repurchase. The method used in this research is explanatory research with a quantitative approach. The population in this study are all consumers who have purchased products at an unknown number of KFC Cempaka Putih Branch restaurants. The sample of this study was 104 people who came from consumers buying products at the KFC Cempaka Putih Branch restaurant. The data collection technique in this study was to use a questionnaire. Then, the data was analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method using the WarpPLS 7.0 program. The results of this study indicate that product quality and customer-perceived value have a positive and significant effect on customer satisfaction. Customer satisfaction, and customer perceived value have a positive and significant effect on repurchase buying. The implications of the study for managerial practices at KFC Cempaka Putih Branch are discussed. Recommendations are made to improve product quality, enhance perceived value, and effectively manage customer satisfaction to foster repurchases.